Estudio de prefactibilidad para la instalación de un hotel lodge ecológico premium en Madre de Dios - Bellido Caffo, Manuel Alejandro (2019)
This work seeks to determine the technical, economic and market feasibility for the implementation of a premium lodge hotel, with an ecological focus, in the Madre de Dios region, applying various industrial engineering methods for its development, in order to be able build it in the future. In the first chapter the problem, the research objectives, the scope and limitations, the justification of the topic and the hypothesis obtained are presented. In the second chapter, the methodology to be used in the research is determined, as well as a projection of the demand of the target audience based on the number of overnight stays per day, the analysis of the offer established in the region to determine the specific demand of the project and marketing strategy of the service. In the third chapter, the location of the service is selected, through an analysis of the relevant factors. In the fourth chapter, the dimension of the service is selected according to different factors, such as the market, resources, technology, investment and balance point, to determine the appropriate plant size. In the fifth chapter, project engineering is explored, with an emphasis on the hotel process, the ecological technologies that will be used, the level of quality required and the environmental impact of this project. The sixth chapter presents the organizational structure of the lodge hotel and its mode of organization. In the seventh chapter the investment tables are presented, as well as the costs and budgets of the project, to determine the economic viability and return on investment of the project, evaluating these results in the eighth chapter to determine how profitable and sensitive the project is. In the ninth chapter, a social evaluation of the project is carried out, in order to draw conclusions and recommendations in chapters ten and eleven.